2017
DOI: 10.4236/ojog.2017.71003
|View full text |Cite
|
Sign up to set email alerts
|

Contraception and Venous Thromboembolism: Risk Factors and Clinical Considerations

Abstract: Venous thromboembolism (VTE) is a known risk with some forms of hormonal contraception, and should be considered by health care providers when counselling patients about their contraceptive options. Various other risk factors exist for VTE, including family history of VTE and a personal history of VTE or thrombophilia. This article will summarize various known risk factors for VTE, as well as what is known about the VTE risk imparted by the use of different contraceptives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Again, this effect can lead to either an increase or decrease in gene expression of clotting factors. It has also been reported that a higher dose of estrogen in oral contraceptives can lead to hypercoagulation disorders . All of these factor stimulations may lead to the formation of a thrombus or pulmonary embolus or preclusion of clot breakdown that could lead to stroke.…”
Section: The Bridge Between Migraine and Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Again, this effect can lead to either an increase or decrease in gene expression of clotting factors. It has also been reported that a higher dose of estrogen in oral contraceptives can lead to hypercoagulation disorders . All of these factor stimulations may lead to the formation of a thrombus or pulmonary embolus or preclusion of clot breakdown that could lead to stroke.…”
Section: The Bridge Between Migraine and Strokementioning
confidence: 99%
“…It has also been reported that a higher dose of estrogen in oral contraceptives can lead to hypercoagulation disorders. 132 All of these factor stimulations may lead to the formation of a thrombus or pulmonary embolus or preclusion of clot breakdown that could lead to stroke. As mentioned earlier, estrogen also has the ability to modulate the glutaminergic system that leads to neuronal excitability and can result in excitotoxicity.…”
Section: ■ Migrainous Infarctionmentioning
confidence: 99%
“…Excess coagulation factor activation favors fibrin clot formation on vascular tissue [29], consequently leading to the development of thrombosis [22, 30]. Although it is possible that these results were affected by the testosterone experiment happening at the same time as ours, research has already shown that the use of hormonal contraceptives is associated with alterations in blood coagulation factors [810]. It is important to mention that the platelet number remained high until the fourth menstrual cycle of the CHC phase, but the values decreased during the fifth cycle.…”
Section: Discussionmentioning
confidence: 94%
“…However, despite the benefits, some side effects of the contraceptives can pose a serious threat to the users' health [ 8 ]. For example, an increase in susceptibility has been noticed for strokes (AVC) [ 8 , 9 ], heart disease [ 10 ], pulmonary embolism [ 11 ], and breast tumors [ 12 ]. The side effects of contraceptives are especially concerning when considering their effects on blood coagulation factors, since many studies directly associate the use of hormonal contraceptives with an increase in thrombosis risk [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation